Imagining a Common Horizon for Humanity and the Planet - Karasar, Hasan Ali; Oğuz, Şafak (2023)
Global problems, such as climate change and past and potential pandemics place a heavy burden on humanity and our planet. We need the cooperation of scientists and philosophers from all disciplines in order to seek and find paths out of these crises. Turkey is at an advantageous if not a central position in forging such a cooperation. We are at the eastern end of the West, western end of the East, and located between the North and the South as well. This book is the outcome of a project titled Imagining a Common Horizon for Humanity and the Planet undertaken by Cappadocia University. In it, you will find chapters by distinguished scholars and philosophers from a multitude of countries, cultural backgrounds and disciplines. We hope the knowledge and the wisdom accmnulated via this project and presented between the covers of this book will provide one more step in reaching an actionable cornmon horizon and contribute to a safer and better world for our children.